Geographies of Forced Eviction : Dispossession, Violence, Resistance - Brickell, Katherine; Fernández Arrigoitia, Melissa; Vasudevan, Alexander (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This book offers a close look at forced evictions, drawing on empirical studies and conceptual frameworks from both the Global North and South. It draws attention to arenas where multiple logics of urban dispossession, violence and insecurity are manifest, and where wider socio-economic, political and legal struggles converge. The authors highlight the need to apply emotional and affective registers of dispossession and insecurity to the socio-political and financial economies driving forced evictions across geographic scales. The chapters each consider the distinct urban logics of precarious housing or involuntary displacements that stretch across London, Barcelona, Rio de Janeiro, Shanghai and Colombo. A timely addition to existing literature on urban studies, this collection will be of great interest to policy makers and scholars of human geography, development studies, and sociology.- Resumé vydavatel